Cholesterol depletion by methyl-beta-cyclodextrin augments tamoxifen induced cell death by enhancing its uptake in melanoma - Mohammad, Naoshad; Malvi, Parmanand; Meena, Avtar Singh; Singh, Shivendra Vikram; Chaube, Balkrishna; Vannuruswamy, Garikapati; Kulkarni, Mahesh J.; Bhat, Manoj Kumar (Molecular Cancer, 2014)
Background: Despite modern advances in treatment, skin cancer is still one of the most common causes of death in the western countries. Chemotherapy plays an important role in melanoma management. Tamoxifen has been used either alone or in-combination with other chemotherapeutic agents to treat melanoma. However, response rate of tamoxifen as a single agent has been comparatively low. In the present study, we investigated whether treatment with methyl-beta-cyclodextrin (MCD), a cholesterol depleting agent, increases the efficacy of tamoxifen in melanoma cells. Methods: This was a two-part study that incorporated in vitro effects of tamoxifen and MCD combination by analyzing cell survival, apoptosis and cell cycle analysis and in vivo antitumor efficacy on tumor isografts in C57BL/6J mice. Results: MCD potentiated tamoxifen induced anticancer effects by causing cell cycle arrest and induction of apoptosis. Sensitization to tamoxifen was associated with down regulation of antiapoptotic protein Bcl-2, up-regulation of proapoptotic protein Bax, reduced caveolin-1 (Cav-1) and decreased pAkt/pERK levels. Co-administration of tamoxifen and MCD caused significant reduction in tumor volume and tumor weight in mice due to enhancement of drug uptake in the tumor. Supplementation with cholesterol abrogated combined effect of tamoxifen and MCD. Conclusion: Our results emphasize a potential synergistic effect of tamoxifen with MCD, and therefore, may provide a unique therapeutic window for improvement in melanoma treatment.
Keywords: Caveolin-1; Cholesterol; Methyl beta-cyclodextrin; Tamoxifen

Blends of shellac as nanofiber formulations for wound healing - Vannuruswamy, Garikapati; Rathna, Gundloori Venkata Naga; Gadgil, Bhagyashri Shashikant Thorat; Gadad, Anand Panchakshari (Journal of Bioactive and Compatible Polymers, 2015)
Shellac is being used in food, pharmaceutical, and agricultural industries. It is seldom used for biomedical applications due to its poor mechanical property and instability. We designed thermoresponsive shellac-based bioactive nanofiber mats that mimic extracellular matrix to extend their utility in wound healing. Various blend compositions of shellac, gelatin, and poly(N-isopropylacrylamide) enriched with a bioactive agent, nadifloxacin, were prepared and nanofiber mats were fabricated. The morphology of the nanofiber formation was influenced by the concentration of polymer, drug, and polymer blend composition. Polymer-drug interactions and thermal and crystalline properties of nanofiber mats were analyzed. The shellac/gelatin/poly(N-isopropylacrylamide) blend of composition 3%/7%/3% (w/v) was chosen to evaluate in vitro drug release. Release studies recorded slow, constant, and sustained release for 140h. The release kinetics and mechanism confirmed zero-order release with resultant r(2) values greater than 0.99, and the Korsmeyer-Peppas release exponent (n) was slightly higher than 0.8, which indicated that drug diffusion was anomalous or non-Fickian type and drug release followed diffusion involving chain stretching. Indirect cytotoxicity studies recorded insignificant toxicity against normal human fibroblast cells. In vivo studies demonstrated that drug-loaded nanofiber mats were more suitable for faster tissue regeneration as compared to nanofiber mats without drug and commercial nadifloxacin cream.
Keywords: drug release and mechanism; nanofibers; Shellac; thermoresponsive; tissue regeneration

Development of diagnostic fragment ion library for glycated peptides of human serum albumin: targeted quantification in prediabetic, diabetic, and microalbuminuria plasma by parallel reaction monitoring, SWATH, and MSE - Korwar, Arvind M.; Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Jayaramaiah, Ramesha H.; Bhat, Shweta; Regin, Bhaskaran S.; Ramaswamy, Sureshkumar; Giri, Ashok P.; Mohan, Viswanathan; Balasubramanyam, Muthuswamy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2015)
Human serum albumin is one of the most abundant plasma proteins that readily undergoes glycation, thus glycated albumin has been suggested as an additional marker for monitoring glycemic status. Hitherto, only Amadori-modified peptides of albumin were quantified. In this study, we report the construction of fragment ion library for Amadori-modified lysine (AML), N(epsilon)-(carboxymethyl) lysine (CML)-, and N(epsilon)-(carboxyethyl) lysine (CEL)-modified peptides of the corresponding synthetically modified albumin using high resolution accurate mass spectrometry (HR/AM). The glycated peptides were manually inspected and validated for their modification. Further, the fragment ion library was used for quantification of glycated peptides of albumin in the context of diabetes. Targeted Sequential Window Acquisition of all THeoretical Mass Spectra (SWATH) analysis in pooled plasma samples of control, prediabetes, diabetes, and microalbuminuria, has led to identification and quantification of 13 glycated peptides comprised of four AML, seven CML, and two CEL modifications, representing nine lysine sites of albumin. Five lysine sites namely K549, K438, K490, K88, and K375, were observed to be highly sensitive for glycation modification as their respective m/z showed maximum fold change and had both AML and CML modifications. Thus, peptides involving these lysine sites could be potential novel markers to assess the degree of glycation in diabetes.

Investigation of antiglycation activity of isoprenaline - Kolekar, Yogesh M.; Vannuruswamy, Garikapati; Bansode, Sneha B.; Santhakumari, B.; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J. (RSC Advances, 2015)
Advanced glycation end products (AGEs) are implicated in pathogenesis of diabetes and its complications. In this study, we report the ability of isoprenaline to inhibit the AGE modification of protein by fluorescence spectroscopy and western blotting. Isoprenaline was more effective in inhibiting AGE modification than aminoguanidine, a well known glycation inhibitor. Further, we show that isoprenaline inhibits at Amadori product formation during glycation reaction by various techniques such as MALDI-TOF-MS, LC-MS/MS, and fructosamine assay. Mass spectrometric analysis of the glycation reaction mixture incubated with isoprenaline suggested that it forms adducts with glucose and thus inhibits glycation. The finding of the additional property of isoprenaline of inhibiting glycation suggests that it is a potential candidate for drug repositioning for the treatment of diabetes and its complications, as it is an FDA approved drug.

Molecules with O-acetyl group protect protein glycation by acetylating lysine residues - Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Kashinath, K.; Kesavan, Suresh K.; Bhat, Shweta; Korwar, Arvind M.; Chougale, Ashok D.; Boppana, Ramanamurthy; Reddy, D. Srinivasa; Kulkarni, Mahesh J. (RSC Advances, 2016)
Pharmaceutical intervention for reduction of advanced glycation end products (AGEs) is considered as a therapeutic strategy to attenuate the pathogenesis of diabetes. Many molecules have been reported to possess antiglycation activity, one such example is acetylsalicylic acid (aspirin). It protects proteins from glycation by acetylating the lysine residues. Therefore, in this study we have synthesized and screened molecules containing free N-acetyl, O-acetyl and acetophenone groups. All the selected molecules in this study showed glycation inhibition but interestingly, only molecules with O-acetyl but not N-acetyl and acetophenone groups were capable of acetylating lysine residue. Furthermore, we have demonstrated that pre-acetylation or aspirin treatment prior to the induction of diabetes helps in reducing HbA1c and AGE formation in the streptozotocin induced diabetic mice. Hence pre-acetylation may have an additional therapeutic efficacy of reducing AGE levels in vivo. Incorporation of O-acetyl group into anti-diabetic molecules could be a useful strategy, as it may have an additive effect in reducing AGEs. Identification of such novel acetylating agents represents a new area in the drug discovery process.

Potential dual role of eugenol in inhibiting advanced glycation end products in diabetes: proteomic and mechanistic insights - Singh, Priyanka; Jayaramaiah, Ramesha H.; Agawane, Sachin B.; Vannuruswamy, Garikapati; Korwar, Arvind M.; Anand, Atul; Dhaygude, Vitthal S.; Shaikh, Mahemud L.; Joshi, Rakesh S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J.; Thulasiram, Hirekodathakallu V.; et al. (Scientific Reports, 2016)
Medicinally important genus Ocimum harbors a vast pool of chemically diverse metabolites. Current study aims at identifying anti-diabetic candidate compounds from Ocimum species. Major metabolites in O. kilimandscharicum, O. tenuiflorum, O. gratissimum were purified, characterized and evaluated for anti-glycation activity. In vitro inhibition of advanced glycation end products (AGEs) by eugenol was found to be highest. Preliminary biophysical analysis and blind docking studies to understand eugenol-albumin interaction indicated eugenol to possess strong binding affinity for surface exposed lysines. However, binding of eugenol to bovine serum albumin (BSA) did not result in significant change in secondary structure of protein. In vivo diabetic mice model studies with eugenol showed reduction in blood glucose levels by 38% likely due to inhibition of alpha-glucosidase while insulin and glycated hemoglobin levels remain unchanged. Western blotting using anti-AGE antibody and mass spectrometry detected notably fewer AGE modified peptides upon eugenol treatment both in vivo and in vitro. Histopathological examination revealed comparatively lesser lesions in eugenol-treated mice. Thus, we propose eugenol has dual mode of action in combating diabetes; it lowers blood glucose by inhibiting a-glucosidase and prevents AGE formation by binding to epsilon-amine group on lysine, protecting it from glycation, offering potential use in diabetic management.

Urinary proteome alterations in HER2 enriched breast cancer revealed by multipronged quantitative proteomics - Gajbhiye, Akshada; Dabhi, Raju; Taunk, Khushman; Vannuruswamy, Garikapati; RoyChoudhury, Sourav; Adhav, Ragini; Seal, Shubhendu; Mane, Anupama; Bayatigeri, Santhakumari; Santra, Manas K.; Chaudhury, Koel; Rapole, Srikanth (Proteomics, 2016)
Globally, breast cancer is the second most common cancer among women. Although biomarker discoveries through various proteomic approaches of tissue and serum samples have been studied in breast cancer, urinary proteome alterations in breast cancer are least studied. Urine being a noninvasive biofluid and a significant source of proteins, it has the potential in early diagnosis of breast cancer. This study used complementary quantitative gel-based and gel-free proteomic approaches to find a panel of urinary protein markers that could discriminate HER2 enriched (HE) subtype breast cancer from the healthy controls. A total of 183 differentially expressed proteins were identified using three complementary approaches, namely 2D-DIGE, iTRAQ, and sequential window acquisition of all theoretical mass spectra. The differentially expressed proteins were subjected to various bioinformatics analyses for deciphering the biological context of these proteins using protein analysis through evolutionary relationships, database for annotation, visualization and integrated discovery, and STRING. Multivariate statistical analysis was undertaken to identify the set of most significant proteins, which could discriminate HE breast cancer from healthy controls. Immunoblotting and MRM-based validation in a separate cohort testified a panel of 21 proteins such as zinc-alpha2-glycoprotein, A2GL, retinol-binding protein 4, annexin A1, SAP3, SRC8, gelsolin, kininogen 1, CO9, clusterin, ceruloplasmin, and alpha 1-antitrypsin could be a panel of candidate markers that could discriminate HE breast cancer from healthy controls.
Keywords: 2D-DIGE; Biomedicine; Breast cancer; HER2 enriched; SWATH; Urinary biomarkers